Brønsted acid catalyzed remote C6 functionalization of 2,3-disubstituted indoles with β,γ-unsaturated α-ketoester - Zhang, You-Ya; Li, Lin; Zhang, Xiang-Zhi; Peng, Jin-Bao (Frontiers in Chemistry, 2022)
Graphical Abstract